THE PROGNOZ SILVER-POLYMETALLIC DEPOSIT, SAKHA (YAKUTIA): CHEMISTRY AND ZONING OF ORE VEINS - Gamyanin G.N.; Anikina E.Yu.; Bortnikov N.S.; Alpatov V.V. (My University, 2003)
The chemical composition of minerals and their distribution in ore bodies of the Prognoz silver-polymetallic deposit has been studied. The deposit is one of the largest in northeast Russia, and its mineralogy is characterized by a great variety of mineral types and isomorphism of some elements in minerals. Amidst minerals with the alternate composition, there are arsenopyrite with varying Ni and Sb content and pyrite with greatly varying As concentration. Nearly complete isomorphous series of minerals stannite-kesterite and tetrahedrite-freibergite have been revealed. Replacement of Sb and Bi in the possible isomorphous series andorite-gustavite and miargyrite-aramayoite is discussed. Both lateral and vertical zoning in the distribution of minerals and the change in their properties are clearly evident in the deposit. The vertical zoning is the most pronounced; it is determined by the confinement of late-stage Ag-bearing assemblages to upper levels of the deposit and manifests itself in changing carbonate and sphalerite ferruginosity, the Ag content in sulfosalts, and the trace element content in quartz. Mineralogical features indicate wavelike zoning. The zoning of silver-polymetallic deposits of eastern Yakutia has been described for the first time. The complicated nature and heterogeneity of the mineral composition, wide variations in isomorphism with coexistence of phases of different composition, and numerous exsolution structures confirm a complicated genesis of the deposit, as was previously suggested by the authors.